1994
DOI: 10.1103/physrevlett.72.2081
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic dynamical scaling near the vortex-glass transition of twinnedYBa2Cu3

Abstract: The complex electrical conductivity o (u) is determined from the linear ac susceptibility between 3 Hz and 3 MHz measured in fields between 0.4 and 12T parallel and perpendicular to the c axis of a twinned crystal. Dynamical scaling of ] o [ and o "/o' reveals ordering temperatures Ts(B) and field-independent scaling functions by using the variable (T,z Ts)/ -[T Ts[. F-or B J c, the critical exponents v and z agree with values obtained on films indicating isotropic vortex-glass fluctuations, whereas those for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 31 publications
4
23
1
Order By: Relevance
“…The ratio of the critical exponents, t/sϭ2.0Ϯ0.4, observed experimentally in YBa 2 Cu 3 O 7Ϫ␦ single crystals 8,9 and ceramics 38 is consistent with the critical exponents for bond percolation on a 3D lattice, 24 t/sϭ2.60Ϯ0.14. This is particularly surprising since the percolating vortices in superconductors are line objects, whereas point particles are assumed in the simulations of bond percolation models.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…The ratio of the critical exponents, t/sϭ2.0Ϯ0.4, observed experimentally in YBa 2 Cu 3 O 7Ϫ␦ single crystals 8,9 and ceramics 38 is consistent with the critical exponents for bond percolation on a 3D lattice, 24 t/sϭ2.60Ϯ0.14. This is particularly surprising since the percolating vortices in superconductors are line objects, whereas point particles are assumed in the simulations of bond percolation models.…”
Section: Discussionsupporting
confidence: 53%
“…16 A semiquantitative agreement was found for ac susceptibility measurements on Bi 2 Sr 2 CaCu 2 O 8 single crystals 17 and for vibrating reed measurements on YBa 2 Cu 3 O 7Ϫ␦ single crystals and films. 18 Reed et al 8 and Kötzler et al 9,10 showed that the extended TAFF model was in quantitative agreement with the frequency-dependent ac susceptibility of Y-1:2:3 single crystals and films near T c , whereas the ac susceptibility at lower temperatures was in agreement with the existence of critical fluctuations around a vortex glass transition temperature T g .…”
Section: Introductionsupporting
confidence: 49%
See 2 more Smart Citations
“…For a short cylinder with heigth h = 2a the radius must be replaced by a/ √ 2 2 . The complex conductivity σ(ω) is obtained from the measured susceptibility χ(ω) by means of an inversion routine [24]. The average Ohmic resistivity at 10 Hz and T > T c is found to be ρ n = (0.5±0.1) nΩm, confirming the purity of the samples and the specification of the manufacturers of RRR ≃ 300.…”
Section: Bulk Superconductivitymentioning
confidence: 79%